Prediction of axial compressor blade excitation by using a two-way staggered fluid-structure interaction model. (June 2018) - Brandsen, Jacobus D; van der Spuy, Sybrand J; Venter, Gerhard
A vibration excitation system has been developed to excite the rotor blades of an axial compressor, in the specified nodal diameter mode and at the specified frequency, by injecting additional compressed air into the compressor flow path. The system was fitted to the Rofanco compressor test bench at the University of Stellenbosch in South Africa. A two-way staggered fluid–structure interaction (FSI) model was constructed that was capable of simulating the vibrations of the rotor blades excited by the vibration excitation system. The results of the FSI simulations were verified using available experimental data. It was concluded that the FSI model is able to recreate the vibrations of the rotor blades with sufficient accuracy. The results of the FSI simulations also indicated that the vibration excitation system should be capable of exciting the blades in the selected mode shape and at the selected frequency, provided the excitation frequency is close to the natural frequency of the first bending mode of each rotor blade.